Supported liquid membrane-coupled Extraction - Shengjie Hu; Xiantao Shen; Chuixiu Huang (Advances in Sample Preparation, 2025)
Group separation of multiple analytes with diverse physicochemical properties from the same complex sample is significant in clinical diagnosis, environmental monitoring and biomarker identification. To achieve this goal, supported liquid membrane (SLM)-coupled extraction techniques were developed by integrating two or more SLM-based extraction processes, either simultaneously or sequentially. This approach offers several advantages such as low sample consumption, short operational time, and efficient group separation. In recent years, SLM-coupled extraction approaches have been successfully applied to extract multiple targets from complex biological samples and environmental samples. However, the reviews in the literature mainly focused on a single SLM extraction technique, either liquid-phase microextraction (LPME) or electromembrane extraction (EME). Therefore, a comprehensive overview of SLM-coupled extraction techniques is still lack. The current review comprehensively summarizes the advances in SLM-coupled extraction techniques. We elaborate three types of SLM-coupled extraction techniques, including coupled-LPME, coupled-EME and EME/LPME. Moreover, a prospective discussion on the future development trends of the SLM-coupled extraction techniques is also provided.